Entrepreneurial Behaviour and Constraints Encountered by Dairy and Poultry Entrepreneurs in Jammu Division of J&K State - Bhavana Gupta , S.K. Kher , and M.S.Nain, (Indian Journal of Extension Education, 2013)
The investigation on 60 entrepreneurs, thirty each selected from dairy and poultry entrepreneurs from Jammu and Kathuadistricts or J & K state revealed that majority of the entrepreneurs had medium level of achievement motivation, risktaking behaviour, decision making ability, communication skills, adoption propensity and self confidence. Poultryentrepreneurs had more internal locus of control than dairy entrepreneurs. Overall entrepreneurial behaviour index washigh in case of poultry entrepreneurs. The major constraints identified in case of dairy entrepreneurs were high initialinvestments (80%), costly veterinary medicines and treatment (66.66%), frequent prevalence of diseases (63%), lack ofstorage facilities (60%) and lack of knowledge about balanced diet (53%). In case of poultry entrepreneurs, high mortalityrate (73.33%), high cost of good quality feed (60%), difficulty in borrowing loans (53.33%), lack of technical guidance(50%) and lack of knowledge about causes and treatment of diseases (46.66%) were the major constraints reported by theentrepreneurs.